PENGARUH VOLUNTARY DISCLOSURE OF FINANCIAL AND CAPITAL MARKET DATA DAN KEPEMILIKAN KELUARGA TERHADAP MANAJEMEN LABA - Fairus Reyna Imayanti (2020)
The purpose of this research is to determine the effect of voluntary disclosure of financial and capital market data (FCMD) and family ownership of earnings management. This research also uses leverage, profitability, and firm size as control variables. The earnings management in this study was measured using Kasznik and Modified Jones Model measurement. The population in this research is manufacturing companies listed on the Indonesia Stock Exchange in the period 2016 - 2018. The amount of sample is 399 companies for every model. Hypothesis testing in this test uses Linear Regression Panel Data with Stata version 13. The results of the test show that, voluntary disclosure of financial and capital market data and family ownership had no influence on earnings management.